More than life itself : a synthetic continuation in relational biology - Louie, Aloisius Ho-Yin (Categories (Frankfurt am Main, Germany), 2009)
A. H. Louie's More Than Life Itself is an exploratory journey in relational biology, a study of life in terms of the organization of entailment relations in living systems. This book represents a synergy of the mathematical theories of categories, lattices, and modelling, and the result is a synthetic biology that provides a characterization of life. Biology extends physics. Life is not a specialization of mechanism, but an expansive generalization of it. Organisms and machines share some common features, but organisms are not machines. Life is defined by a relational closure that places it be.